2014
DOI: 10.2355/isijinternational.54.1667
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Carbide Precipitation in a H21 Tool Steel

Abstract: Carbide precipitation in a H21 tool steel during conventional heat treatment was studied. The aim of this work was to study the exact microstructure and for better understanding of carbide formation during double tempering process of the H21 tool steel. The steel was austenised either at 1 100°C or 1 250°C for 1 hour, and water quenched. Double tempering was performed at 650, 750 and 800°C for 1 hour with air cooling in the first and second temper for each austenising temperature. The results showed that the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 16 publications
2
15
0
Order By: Relevance
“…The chromium content in the M 7 C 3 carbides was lower at an austenizing temperature of 1250°C than at an austenizing temperature of 1100°C when the same aging temperature was used, which indicated that the M 7 C 3 carbides in the sample austenized at the higher temperature were not stable at an aging temperature of 650°C. This finding is consistent with the results of a previous study [6] in which the authors reported that a higher austenizing temperature accelerated the carbides' approach to equilibrium. The evolution of the chemical composition of the M 6 C carbides was different than that of the M 7 C 3 carbides.…”
Section: Effect Of Double-aging Treatment On Microstructuresupporting
confidence: 95%
See 3 more Smart Citations
“…The chromium content in the M 7 C 3 carbides was lower at an austenizing temperature of 1250°C than at an austenizing temperature of 1100°C when the same aging temperature was used, which indicated that the M 7 C 3 carbides in the sample austenized at the higher temperature were not stable at an aging temperature of 650°C. This finding is consistent with the results of a previous study [6] in which the authors reported that a higher austenizing temperature accelerated the carbides' approach to equilibrium. The evolution of the chemical composition of the M 6 C carbides was different than that of the M 7 C 3 carbides.…”
Section: Effect Of Double-aging Treatment On Microstructuresupporting
confidence: 95%
“…(5) The approach of carbides to their equilibrium composition during double-aging was strongly affected by the austenizing temperature. (6) The maximum hardness of the double-aged H23 tool steel (448 HV) was achieved via austenization at 1250°C followed by double-aging at 650°C.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, reports about carbides mainly focused on the heat treatment stage. [7][8][9] However, during heat treatment stage, it was dif cult to eliminate defects caused by primary carbides. 10) Primary carbides can also precipitate during ESR process.…”
Section: Introductionmentioning
confidence: 99%